Student Assessment of Problem-based Learning: differences by gender - Carmona Martínez, Mercedes; Conesa Pérez, María del Carmen; Ros Clemente, María Isabel (Historia y Comunicación Social, 2014)
This research aims to evaluate the application of Problem Based Learning (PBL) methodology in response to students’ gender. Numerous investigations observe differences in learning styles and strategies as for gender that can influence the assessment of a particular teaching method. After conducting a survey which evaluates the effectiveness of applied learning procedures, we find that despite contrast was made by equal average in most cases, the differences were not significant in terms of student gender in such assessment.
Keywords: Problem-based learning; teaching methodology; gender differences.